At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
x = 5 - 3y
x = 2y - 10
5 - 3y = 2y - 10
+ 3y + 3y
5 = 5y - 10
+ 10 + 10
15 = 5y
5 5
3 = y
x = 2y - 10
x = 2(3) - 10
x = 6 - 10
x = -4
(x, y) = (-4, 3)
x = 2y - 10
5 - 3y = 2y - 10
+ 3y + 3y
5 = 5y - 10
+ 10 + 10
15 = 5y
5 5
3 = y
x = 2y - 10
x = 2(3) - 10
x = 6 - 10
x = -4
(x, y) = (-4, 3)
y=3
x=-4
you have to use substitution. so instead of the equations having two variables, they will now have one.
5-3y=2y-10 after solving for y, plug the answer in any of the equations and you will find x.
x=-4
you have to use substitution. so instead of the equations having two variables, they will now have one.
5-3y=2y-10 after solving for y, plug the answer in any of the equations and you will find x.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.